Organizing Science in Society: The conduct and justification of responsible research - Cecilie Glerup (Copenhagen Business School (CBS), 2015)
Within the last couple of decades, a range of new concepts that all propose that science should be done `more responsibly' has emerged within science governance literature as well as in science government in both the USA and across Europe. Terms such as `Responsible Innovation' (Owen et al. 2013) and `socially robust science' (Nowotny, Scott, and Gibbons 2001) have gained momentum within science governance. Generally speaking, the calls share the view that there is a need for more external governing of science as a vital supplement to the internal professional ethics that also guide scientific conduct (Braun et al. 2010; Jasanoff 2011). Moreover, they agree that there is a need to enhance scientists' abilities to reflect upon the `outcomes' of their inventions – that is, the social, environmental and ethical consequences of introducing new scientific knowledge and technologies into society. Though the calls for `Responsible Science' are plentiful, few have actually studied how `Responsible Science' is done in practice and how the demands affect the scientific work, i.e. the organisation of science, the scientists' professional identities and their wellbeing at work. This dissertation examines how public scientists relate to current demands for `Responsible Science'. Based on a Foucauldian-inspired document study of scientific journal papers as well as an STS-inspired ethnographic study of two laboratories, it answers the research questions: How is `Responsible Science' conducted and justified by public scientists – and what are the consequences of these responsibilities in their daily work?
hdl:10398/9128
Keywords: 650